Does Firm Investment Respond to Peers’ Investment? - Bustamante, M. Cecilia; Frésard, Laurent (Management Science, 2021)
We study whether, how, and why the investment of a firm depends on the investment of other firms in the same product market. Using an instrumental variable based on the presence of local knowledge externalities, we find a sizeable complementarity of investment among product market peers, holding across a large majority of sectors. Peer effects are stronger in concentrated markets, featuring more heterogeneous firms, and for smaller firms with less precise information. Our findings are consistent with a model in which managers are imperfectly informed about fundamentals and use peers’ investments as a source of information. Product market peer effects in investment could amplify shocks in production networks. This paper was accepted by Gustavo Manso, finance.